2004
DOI: 10.1111/j.1365-2494.2004.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed‐set and pollen–stigma compatibility in Leymus chinensis

Abstract: Chinese leymus [Leymus chinensis (Trin.) Tzvel.] is an important forage distributed in East Asia. The seed-set rates and the pollen-stigma compatibility in six populations were investigated in 2001. Proportionately seed-set ranged from 0AE065 to 0AE567 under open pollination and 0AE0056 to 0AE0426 under self-pollination. The former is significantly higher than the latter in each population. Microscopic observations showed that proportionately only 0AE0551 to 0AE1167 of self-pollinated pollen grains were compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…It is a self-incompatible species, which often enforces outcrossing and may have increased the geographic distribution of genetic diversity [9]. Sheepgrass has diverse environmental adaptations and can grow across diverse soil and climate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is a self-incompatible species, which often enforces outcrossing and may have increased the geographic distribution of genetic diversity [9]. Sheepgrass has diverse environmental adaptations and can grow across diverse soil and climate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to the self-adjusting of L. chinensis for the highly adaptation to alkaline-sodic soils (pH 8.5-11.5) (Zhang et al, 2004;Jin et al, 2006;Jin et al, 2008;Chen and Wang, 2009). …”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…chinensis, a native, perennial rhizomatous grass with high palatability and forage value, is one of the dominant species in grassland of northern China, including Songnen Grassland Liu et al, 2004) and part of the Inner Mongolia Steppe Wang et al, 2010). L. chinensis is capable of growing in various environments, such as drought, low temperature, and highly alkaline-sodic (pH 8.5-11.5) soils (Zhang et al, 2004;Jin et al, 2006;Jin et al, 2008;Chen and Wang, 2009). …”
Section: Introductionmentioning
confidence: 97%
“…Our previous study revealed that sheepgrass is a GSI species, in which most self-pollinated pollen grains are incompatible but cross-pollinated pollen grains are compatible, and the seed-set range of sheepgrass ranges from 6.50% to 56.70% under cross-pollination and from 0.56% to 4.26% under self-pollination [48]. Subsequently, a transcriptomic analysis of mature stigmas, mature ovaries, and leaves were carried out and 1025 sheepgrass stigma-specific or preferentially expressed genes were identified in our laboratory [49].…”
Section: Introductionmentioning
confidence: 99%